2021
DOI: 10.3390/ijerph18189533
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Significantly Impacts the Haematological Variables of the Athlete Biological Passport

Abstract: In the fight against sports doping, the Athlete Biological Passport (ABP) system aims to indirectly unveil the doping incidents by monitoring selected biomarkers; however, several unexplored extrinsic factors may dampen a fair interpretation of ABP profiles. Chinese herbal medicine (CHM) plays a pivotal role in the health care system, and some remedies have a long history of being used to treat anaemia. In this study, we addressed the concerns of whether the CHM administration could yield a measurable effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 43 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Astragalus membranaceus supplementation was found to improve the subjects' aerobic performance, oxidative status, reticulocytes percentage, and response to acclimatization [12,14,21] without a specific effect on the athletes' strength [11]. The results of studies in which Astragalus was co-administered with other remedies showed similar results (see Table 1).…”
Section: Description Of the Included Studiesmentioning
confidence: 92%
See 4 more Smart Citations
“…Astragalus membranaceus supplementation was found to improve the subjects' aerobic performance, oxidative status, reticulocytes percentage, and response to acclimatization [12,14,21] without a specific effect on the athletes' strength [11]. The results of studies in which Astragalus was co-administered with other remedies showed similar results (see Table 1).…”
Section: Description Of the Included Studiesmentioning
confidence: 92%
“…Overall, 529 articles (PubMed: 59; EMBASE: 111; Web of Science: 117; Cochrane Library: 26; Google Scholar: 216) were screened, and 11 of them were considered eligible for inclusion in this systematic review [11][12][13][14][15][16][17][18][19][20][21]. The most important characteristics of these studies are summarized in Table 1.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations